Automatic mesoscopic fracture modelling of concrete based on enriched SBFEM space and quad-tree mesh. (3rd October 2022) - Jiang, Shouyan; Sun, Liguo; Ooi, Ean Tat; Ghaemian, Mohsen; Du, Chengbin
Highlights: The methods by combining enriched SBFEM with quad-tree mesh are proposed to simulate crack propagation of concrete. An improved random aggregate model is proposed to construct mesoscale concrete models. The whole mesh generation process is highly efficient without any artificial interference. Local remeshing is unnecessary as crack propagates. Abstract: A novel approach for mesoscale modelling of concrete composites is proposed by combining enriched scaled boundary finite element methods with quad-tree mesh. The concrete meso -structures are comprised of randomly distributed aggregates, mortar matrix, and interface transition zone. An improved random aggregate generation technique is developed to construct digital images of mesoscale concrete models. Based on the quadtree decomposition algorithm, meshes can be generated automatically from the digital images of concrete mesostructure. The whole mesh generation process is highly efficient without any artificial interference and eliminates the issue of hanging nodes faced by standard finite elements. Additionally, local remeshing is unnecessary as crack propagates. Three numerical examples are modelled to demonstrate the performance of the proposed approach, and the effects of aggregate area fraction on the mechanical properties of concrete composites are also discussed.